SOCIAL RESISTANCE OF THE SANGIHE PEOPLE IN THE NOVEL OF PEREMPUAN YANG MENUNGGU DI LORONG MENUJU LAUT BY DIAN PURNOMO - Nur Wahyudin, Sapta Arif; Qibtiah, Mariatul; Sutejo, Sutejo (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Dian Purnomo tells the story of the struggle of the Sangihe residents in her novel entitled Perempuan yang Menunggu di Lorong Menuju Laut. Social resistance in the novel is studied using Scott's theory of social resistance. The research method used was descriptive qualitative and literature analysis. The research results found forms of social resistance of the Sangihe people in the novel, (1) oration; (2) petition; (3) demo; (4) sue; and (5) blocking the road. The type of resistance carried out by the Sangihe people based on Scott's theory of resistance is open resistance. The type of social resistance carried out by the Sangihe people, based on Scott's theory of resistance, is open resistance. A resistance that aims to confront two opposing parties. This novel teaches not to give up quickly and to continue fighting to do the right thing without fear. That natural wealth should be preserved and protected. And human rights to maintain survival must not be violated in any form.